Analysis of community-based ecotourism impact of Wae Bobok on the social and economic life in Tanjung Boleng Village Manggarai Barat Regency - Saryani, Saryani; Fajriati, Andi; Nugroho, Setyo Prasiyono; Santosa, Santosa (Technium Social Sciences Journal, 2022)
One of the community-based ecotourism sectors which are growing in Manggarai Barat is Wae Bobok ecotourism which is located in Tanjung Boleng Village. This sector is being thought to have a strategic role to boost the economy that is believed as one of the ways to make the community prosper. Wae Bobok Ecotourism is an activity that directly involved the local community so it can give an impact on its people. The purpose of this research is to acknowledge the condition of Wae Bobok Ecotourism and to know the impact of community-based Wae Bobok Ecotourism on the social life and economy in Tanjung Boleng Village Manggarai Barat Regency. This research is using descriptive qualitative method. The determination of informants, with purposive sampling, are the local people in Desa Tanjung Boleng, the organizers, the headman and the Department of Tourism and Culture of Manggarai Barat Regency. Observation, interview, and documentation are used for the data collection technique. The result of the research shows that the existence of Wae Bobok Ecotourism has positively impacted the social life and economy of the local people in Tanjung Boleng Village, specifically: the transformation of jobs from unemployed to employed, the increase of skills and knowledge, the escalation of social interactions, widening the employment, the increase of revenue with the business opportunities. Besides the positive impacts that the local people of Tanjung Boleng Village experience, evidently exist the negative impacts which are the decreasing of the traditional value of gotong royong (mutual cooperation), the economic dependence whereupon economy dependence happens to the local people that do not have stable jobs who can only work as merchants and the incomes gap between the local people who involved in ecotourism with the people who do not get involved in the ecotourism of Wae Bobok.